Bio-inspired composite films with integrative properties based on the self-assembly of gellan gum–graphene oxide crosslinked nanohybrid building blocks. (September 2015) - Kang, Ding; Cai, Zhixiang; Jin, Qiangwei; Zhang, Hongbin
Abstract: Mimicking natural structures to synthesize novel structural materials is attracting considerable attention, but progress in practical applications remains slow. Natural composites achieve excellent balance between strength and toughness from the "brick-and-mortar" arrangement of organic and inorganic layers, accompanied with various toughening mechanisms. We emulate the structural features of natural nacre by combining graphene oxide (GO) and a gellan gum (GG) biopolymer. We also reveal the mechanism of integrative mechanical performance. Several GO nanosheets with GG coating and crosslinking are used as optimal building blocks with intrinsic hard/soft features. These materials are induced to rapidly self-assemble into aligned nacre-like films by vacuum filtration to produce strong and tough bio-inspired composite films with fracture strength of 88.7 MPa, fracture stain of 0.84%, tensile modulus of 25.4 GPa and good biocompatibility. This study has merit of unrestricted fabrication of a homogeneous colloidal suspension of crosslinked nanohybrid building blocks of GO. Composite films constructed using these building blocks are innovative because of combined interactions, including coordination bonding, ionic bonding, and hydrogen bonding among their constituents. These films differ from other reported bio-inspired GO composite films with single adhesion interaction and thus provide good integrative mechanical performance through a multiple energy dissipation mechanism.